Análise da expressão de genes relacionados à defesa em novos híbridos de citros resistentes à Clorose Variegada dos Citros e mapeamento de eQTL - Mauricio, Fernanda Nara (Universidade Federal de São Carlos, 2013)
Brazil is the largest producer of sweet orange, but the productivity is not the highest due to disease problems. A major problem is the Citrus Variegated Chlorosis (CVC) caused by the bacterium Xylella fastidiosa, which promotes obstruction of the xylem, causing physiological disorders in plant and in advanced cases, affecting fruits, leading to production losses. In this study, hybrids obtained from controlled crosses between Murcott tangor [Citrus reticulata Blanco x Citrus sinensis (L.) Osbeck] and Pera sweet orange [Citrus sinensis (L.) Osbeck] were evaluated by analysis of symptoms, diagnosis through conventional and real time PCR (Polymerase Chain Reaction) , showing seven resistant hybrids, twenty-four tolerant hybrids and six susceptible hybrids. The expressions of thirteen genes [NBS-LRR - RGH1, Abscisic Acid (ABA), Thaumatin, Chitinase, Xa21 Kinase, Kinase CHRK1, Isoflavone Synthase, Protein Defense-Related Resistance - DRRP, No Product Set - SPD, Isoflavone Reductase, HCr2-0A, Ankyrin, Glutathione GST-22 associated with resistance were evaluated, and it was possible to relate the resistance to X. fastidiosa with gene expression. QTL (Quantitative Trait Loci) were mapped through the quantification of symptoms and bacterial concentration and expression QTL (eQTL) of genes were carried out with the evaluation of thirty-seven hybrids.
Analysis of defense-related gene expression in new citrus hybrids resistant to Citrus Variegated Chlorosis and eQTL mapping
Keywords: Mapeamento genético; Clorose Variegados Citros; Melhoramento genético; CVC; Genetic mapping; Genetic breeding; CIENCIAS AGRARIAS